Rapid determination of quetiapine in blood by gas chromatography–mass spectrometry. Application to post‐mortem cases. Issue 10 (11th October 2013) - López‐Guarnido, Olga; Tabernero, María Jesús; Hernández, Antonio F.; Rodrigo, Lourdes; Bermejo, Ana M.
ABSTRACT: A simple, fast and sensitive method for the determination of quetiapine in human blood has been developed and validated. The method involved a basic liquid–liquid extraction procedure and subsequent analysis by gas chromatography–mass spectrometry, previous derivatization with bis (trimethylsilyl)‐trifluoro‐acetamide and chorotrimethylsilane (99 : 1). The methods of validation included linearity with a correlation coefficient > 0.99 over the range 0.02–1 µg ml –1, intra‐ and interday precision (always < 12%) and accuracy (mean relative error always < 12%) to meet the bioanalytical acceptance criteria. The limit of detection was 0.005 µg ml –1 . The procedure was further applied to post mortems from the Institute of Legal Medicine, University of Santiago de Compostela. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A simple, fast and sensitive method for the determination of quetiapine (QTP) in human blood has been developed and validated. The method involved a basic liquid‐liquid extraction procedure and subsequent analysis by gas chromatography‐mass spectrometry (GC/MS), previous derivatization with bis(trimethylsilyl)‐trifluoroacetamide (BSTFA) and chorotrimethylsilane (TMCS) (99:1). The method validation included linearity with a correlation coefficient >0.99 over the range 0.02–1 µg mL ‐1 .The limit of detection was 0.005 µg mL ‐1 . The procedure was further applied to post mortem cases.